Problemas particulares de seguridad alimentaria durante el embarazo - Claudia Peñuela; Amy Simonne (EDIS)
FCS8886Span, a 3-page fact sheet by Claudia Peñuela and Amy Simonne, is the Spanish language version of FCS8886/FY1136: Special Food Safety Issues during Pregnancy. It highlights special food safety issues for pregnant women: listeriosis, methylmercury, and toxoplasmosis. Includes references. Published by the UF Department of Family Youth and Community Sciences, December 2009.